Islam Toleran: Membangun Harmoni Beragama Berbasis Spiritual - Putra, Andi Eka; Rohmatika, Ratu Vina (Universitas Islam Negeri Raden Intan Lampung, 2020)
Many methods have been tried and pursued in order to build a tolerant Islam in Indonesia. The various methods that have been tried are dialogue with its various models, ethnic communication, religious harmony, and cooperation. Theoretically, several approaches have been taken and implemented in order to build genuine tolerance. One of the significant and contextual theoretical approaches in building tolerant Islam in Indonesia is through the Sufism approach or the Islamic spiritual path. Spiritual expression emphasizes harmony, openness and acceptance of others which is true, without further ado or false tolerance. Spirituality is the core of diversity in Indonesia that can be offered to the world.